Partisipasi Petani Jagung Dalam Kelompok Tani Untuk Mengakses Kredit Usaha Rakyat : Petani Jagung Dalam Kelompok Tani Untuk Mengakses Kredit Usaha Rakyat - Karlena Arsyad; Zulham Sirajuddin (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
The main objective of this study was to determine the participation of farmers in accessing credits (KUR) in corn farming. The specific objectives of this research are: (1) to identify the diversity of farmers' access to KUR, (2) to identify variables that correlate with farmers' access to KUR, and (3) to identify the active role in farmer’s group (KT) on KUR access. This research was conducted on 104 corn farmers who are members of the Farmers Group in four villages in Bone Bolango District, Gorontalo Province, namely Dumbaya Bulan Village, Butu Village, Tunggulo Village, and Bunuo Village. The results of this study indicate that there are variations in access to KUR by farmers, where farmers generally do not have access to KUR. Among the demographic items, none of the variables correlated with farmers' access to KUR. Meanwhile, the activeness of farmers in KT has a significant effect on increasing farmers' access to KUR.